Oxford student's Dictionary - Ruse, Christina (Nebraska: Oxford University Press)
The Oxford Student's Dictionary is for intermediate to advanced learners of English. It has a particular focus on curricular vocabulary and includes the words you need to study other subjects such as Art, Computing, Science, Geography, History, Literature, Maths, Sport and much more.
1. Ideas into words 2. Using a noun entry
|}005410
Keywords: R, USAGE, SPOKEN ENGLISH|Col. Re